Metaverse Integration in Business: Strategies for Competitive Advantage - Wisnujati, Nugrahini Susantinah; Kamal, Mohammed; Sangadji, Suwandi S. (PT. Sangadji Media Publishing, 2024)
The integration of the metaverse into business operations presents significant opportunities for enhancing competitiveness and innovation. This comprehensive literature review explores recent research trends and findings regarding metaverse integration in various industries. By synthesizing insights from academic studies, industry reports, and case analyses, the study highlights the growing interest in leveraging immersive technologies such as virtual reality (VR) and augmented reality (AR) to redefine business strategies and gain competitive advantages. Key themes include customer engagement, product innovation, collaboration, and monetization strategies within the metaverse economy. Despite promising opportunities, challenges such as accessibility, data privacy, and interoperability standards require careful consideration. Future research should focus on understanding long-term impacts, developing effective monetization strategies, and fostering interdisciplinary collaborations for responsible and sustainable metaverse integration.